An Examination of Mediators of the Transfer of Cognitive Speed of Processing Training to Everyday Functional Performance - Edwards, Jerri D. (2012)
The purpose of these analyses was to examine mediators of the transfer of cognitive speed of processing training to improved everyday functional performance (Edwards, Wadley, Vance, Roenker, & Ball, 2005). Cognitive speed of processing and visual attention (as measured by the Useful Field of View Test; UFOV) were examined as mediators of training transfer. Secondary data analyses were conducted from the Staying Keen in Later Life (SKILL) study, a randomized cohort study including 126 community dwelling adults 63 to 87 years of age. In the SKILL study, participants were randomized to an active control group or cognitive speed of processing training (SOPT), a non-verbal, computerized intervention involving perceptual practice of visual tasks. Prior analyses found significant effects of training as measured by the UFOV and Timed Instrumental Activities of Daily Living (TIADL) Tests. Results from the present analyses indicate that speed of processing for a divided attention task significantly mediated the effect of SOPT on everyday performance (e.g., TIADL) in a multiple mediation model accounting for 91% of the variance. These findings suggest that everyday functional improvements found from SOPT are directly attributable to improved UFOV performance, speed of processing for divided attention in particular. Targeting divided attention in cognitive interventions may be important to positively affect everyday functioning among older adults.